Penerapan Alternatif Akad Pembiayaan Haji dan umrah Pasca Peraturan Menteri No 24 Tahun 2016 Pada Bank Panin Dubai Syariah Surabaya - Fitrotu Aini (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2018)
ABSTRACTHajj as a great symbol of worship. Hajj is the fifth pillar of Islam which is mandatory for every Muslim who are able to da it in accordance with the legal requirement of pilgrimage. One of the legal conditions of Hajj is the capability, capable to cover the cost of the hajj and the family left behind. Panin Bank Dubai Sharia Bank was established based on the regulation of Limited Company No. 12 dated January 8, 1972 by Moeslim Dalidd, a notary in Malang. PT. Bank Panin Dubai Syariah Tbk has been legalized by the Financial Services Authority ("OJK"), in accordance with a copy of the policy of the Board of Commissioners of OJK No. Kep-29 / D.03 / 2016 on July 26, 2016.Therefore, through this research, the writer wants to understand: (1) how is the practice of applying alternative financial agreement of hajj and umrah after the implementation of regulation made by ministry of religious affair No. 24 year 2016 at Panin Bank Dubai Syariah Surabaya branch? (2) What is the analysis of Islamic law on the practice of multilateral contract alternative application in this Bank? Therefore, this study is aimed to, firstly, understand and describe the application of alternative contracts to hajj and umrah after the regulation of Ministry of Religious Affairs No. 24 of 2016 in Panin Bank Dubai Sharia branch Surabaya, and to describe the analysis of Sharia Economic Law about the practice of applying alternative contract in the bank.The method used in this research is qualitative method. The research data are taken in natural situation in Panin Bank Dubai Syariah Surabaya. The data are taken during operational hours using case study approach. Are done through interview technique with the main participant, Assistant Manager 1, and document, archive, book, sample of registration, as secondary data source. The data are analyzed through 3 (three) data deduction, display data and ended with conclusion and verification.The results of the study indicate that the Panin Bank Dubai Sharia runs in accordance with the government regulation No. 24 year 2016 "BPS BPIH is prohibited from providing direct and indirect Hajj money service" including Hajj and Umrah services using various financing products and funds saving, funds collecting in the form of deposits, savings or other forms, using multi-service financing akad wadi'ah, with the savings of hajj services with initial minimum deposit of Rp500,000,and according to customersâ€™ ability.Â Keywords: hajj, umrah, wadi'ah.